Pembelajaran PKN Berbasis Project Dalam Meningkatkan Sikap Gotong Royong Siswa Kelas II SDN Puncaksuji - Ade Saripah; Dyah Lyesmaya; Din Azwar Uswatun (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background of this study is the low attitude of mutual cooperation among grade II students at Puncaksuji Elementary School. The purpose of this research is to describe the planning, implementation, and results of implementing the project model to improve students' mutual cooperation attitude. The research method used is classroom action research. The research design used was Kemmis and Mc Taggart's classroom action research. The subjects of this study were 29 grade II students at SDN Puncaksuji. This research was conducted from February 2023 to June 2023 and was carried out at SDN Puncaksuji, Ciracap District. Data collection techniques used are observation and documentation. The instrument used to collect data is an observation sheet. The data that has been collected is then analyzed using descriptive statistical techniques. The results showed that in the pre-cycle, the score for mutual cooperation was 1.31 and included in the less criteria. In cycle I, the score of the results of the mutual cooperation attitude assessment was 2.53 and included in the good criteria. In cycle II, the score of the results of the mutual cooperation attitude assessment was 3.40 and included in the very good criteria. after doing project-based learning, students showed a very good mutual attitude where most students were active in group work, willing to help friends who were having trouble, willing to do tasks together, not blaming friends if there were mistakes, and respecting friends.